2021
DOI: 10.1101/2021.04.12.21255307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Standard pleural interventions are not high-risk aerosol generating procedures

Abstract: No evidence exists regarding the risk of aerosolisation from pleural procedures. This study used two discrete methodologies, in an environment with no background aerosol interference, to measure aerosol generation from 10 different pleural procedures (3 medical thoracoscopies, 3 indwelling pleural catheter insertions, 1 therapeutic thoracentesis, and 3 indwelling pleural catheter removals). The measurements indicated that, any aerosol production during these procedures was significantly lower than aerosols pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Droplets < 100 μm tend to evaporate after leaving the respiratory air chambers and remain suspended in the air, behaving similarly to aerosols [9]. No unified measurement approach yet exists for aerosols and droplets < 100 μm [3,10], but recent evidence suggests that aerosols and small droplets produced by patients in general, not just AGPs, may be the most important mode of transmission [7,[11][12][13][14][15]. Regardless, the need for inexpensive and bespoke mitigations against virus spreading via aerosols and small droplets is clear.…”
Section: Introductionmentioning
confidence: 99%
“…Droplets < 100 μm tend to evaporate after leaving the respiratory air chambers and remain suspended in the air, behaving similarly to aerosols [9]. No unified measurement approach yet exists for aerosols and droplets < 100 μm [3,10], but recent evidence suggests that aerosols and small droplets produced by patients in general, not just AGPs, may be the most important mode of transmission [7,[11][12][13][14][15]. Regardless, the need for inexpensive and bespoke mitigations against virus spreading via aerosols and small droplets is clear.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of AGPs is questioned by the recent quantitative study of aerosol generation in clinical procedures (such as intubation, pulmonary function testing and noninvasive ventilation), which have been found to be no more aerosol generating than physiological respiratory functions (like tidal breathing and speaking), while coughing has been demonstrated to generate more aerosol than any other procedure investigated. [2][3][4] In a study of oesophago-gastro-duodenoscopy (OGD), which has procedural similarities to TOE; it was found that coughing induced by the procedure (occurring in 60% of participants) resulted in more aerosol generation than their voluntary coughs and tidal breathing. Insertion and removal of the endoscope were not aerosol generating unless a cough was triggered.…”
mentioning
confidence: 99%